2016
DOI: 10.1073/pnas.1523482113
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II super-enhancer increases surface expression of HLA-DR and HLA-DQ and affects cytokine production in autoimmune vitiligo

Abstract: Genetic risk for autoimmunity in HLA genes is most often attributed to structural specificity resulting in presentation of self-antigens. Autoimmune vitiligo is strongly associated with the MHC class II region. Here, we fine-map vitiligo MHC class II genetic risk to three SNPs only 47 bp apart, located within a predicted super-enhancer in an intergenic region between HLA-DRB1 and HLA-DQA1, localized by a genomewide association study of 2,853 Caucasian vitiligo patients. The superenhancer corresponds to an expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 41 publications
(39 reference statements)
2
71
0
Order By: Relevance
“…Detailed analyses on large sample sizes will be needed to disentangle the regulatory effects from the strong amino acid effects. While amino acid changes causing differential antigen display may be the primary autoimmune mechanism at the HLA locus, our data underscores the possibility that expression levels of HLA class II may also play a crucial and unappreciated role (35,36). Over the past several decades, there has been literature suggesting variation in expression among different HLA alleles (26,(37)(38)(39) -but to date the idea that this regulation changes with cell-state has not been established.…”
mentioning
confidence: 69%
“…Detailed analyses on large sample sizes will be needed to disentangle the regulatory effects from the strong amino acid effects. While amino acid changes causing differential antigen display may be the primary autoimmune mechanism at the HLA locus, our data underscores the possibility that expression levels of HLA class II may also play a crucial and unappreciated role (35,36). Over the past several decades, there has been literature suggesting variation in expression among different HLA alleles (26,(37)(38)(39) -but to date the idea that this regulation changes with cell-state has not been established.…”
mentioning
confidence: 69%
“…The Spritz group has shown that for both MHC class I ( HLA-A ) [68,69] and MHC class II ( HLA-DRB1/-DQA1 ) [70,71], the vitiligo-associated causal SNPs are located in transcriptional enhancer elements that up-regulate expression of the corresponding MHC genes, resulting in gain of function. Interestingly, the MHC class II association signal also constitutes a quantitative trait locus (QTL) for vitiligo age-of-onset [72].…”
Section: Genomewide Studiesmentioning
confidence: 99%
“…Of these associations in Chinese, only that in the RNASET2-FGFR1OP-CCR6 region corresponds to an association detected in Caucasian patients [63]. Indeed, while MHC class I and class II region associations were detected in Caucasians [62,65,68,69,71] and Chinese [76], the specific underlying associations appear to be somewhat different. This is surprising, as a GWAS of vitiligo in Japanese [79] detected an MHC class I association with HLA-A*02:01 that appears identical to that in European-derived whites, while an immunocentric GWAS of vitiligo in Asian Indian and Pakistani patients detected an MHC class II association that similar to that European-derived whites [80], though more detailed MHC analysis in Indians [81] found class II association that was the same as in Chinese [76].…”
Section: Genomewide Studiesmentioning
confidence: 99%
“…For TYR 21 , GZMB 53 , and MC1R 7 , principal vitiligo risk derives from missense substitutions, whereas for OCA2 6 and the MHC class I 54 and class II 55 loci principal vitiligo risk is associated with causal variation in nearby transcriptional regulatory elements. To assess the fraction of vitiligo-associated loci for which causal variation is likely regulatory, we carried out conditional logistic regression analysis of all loci to define independent association signals, and for each signal we compiled all variants that could not be statistically distinguished.…”
mentioning
confidence: 99%